Confronting the "good death" : Nazi euthanasia on trial, 1945-1953 - Bryant, Michael S. (2005)
The scholarship devoted to the complicity of German physicians in the Holocaust is rich and detailed, but there remains, as Michael Bryant demonstrates, still more to learn. It is well established that the techniques employed by the Nazis to exterminate Jews and others in concentration camps were first applied to people in state hospitals who were deemed mentally disabled or terminally ill. What has been less thoroughly investigated is the postwar response of both the Allies and the Germans to these atrocities. Bryant fills the gap with a systematic account of the judicial proceedings against those charged with killing the disabled.